Voxel-based analysis of apparent diffusion coefficient in perihaematomal oedema: associated factors and outcome predictive value for intracerebral haemorrhage. Issue 1 (3rd November 2011) - Tsai, Yuan-Hsiung; Hsu, Li-Ming; Weng, Hsu-Huei; Lee, Ming-Hsueh; Yang, Jen-Tsung; Lin, Ching-Po
Abstract : Objectives: The pathophysiology of perihaematomal oedema (PO) surrounding a primary intracerebral haemorrhage (ICH) is complicated and incompletely understood. We prospectively investigated the components of PO with voxel-based analysis of the apparent diffusion coefficient (ADC) value and assessed its predictive value for functional outcome. Design: Forty-six patients with ICH who were enrolled for clinical evaluation underwent MRI scans within 24 h after ICH. Based on the ADC value of the ipsilateral voxels divided by the mean ADC value of the contralateral mirror region of interest, the voxels with oedema were classified into three categories: cytotoxic, vasogenic and undetermined. The percentages of cytotoxic and vasogenic oedema were then calculated and correlated with clinical outcome according to the modified Rankin Scale (mRS) at 6 months after ICH. The intraobserver and interobserver reliability of this method were examined using intraclass correlation coefficients. Results: The intraclass correlation coefficients showed that analysis using the voxel-based method is highly reliable. Among the clinical variables tested, age and serum creatinine levels were positively correlated with percentage of cytotoxic oedema. Age, history of coronary artery disease, National Institutes of Health Stroke Scale score and percentage of cytotoxic oedema were all associated with mRS at 6 months after ICH. Conclusions: The pathophysiological processes within PO are complicated. Voxel-based analysis of ADC values may help to identify the components of PO and may be beneficial for decision making and predicting outcome.